Geology and Basalt Petrogenesis in The Amerrung Area Barru Regency South Sulawesi Province - Adam, Muhammad; Hasanuddin; Violensia (CV Insight Publisher, 2024)
The research location is in the Amerrung area, Barru Regency, South Sulawesi Province. This area is interesting to learn about the geology and petraceability of the basalt. This study aims to determine the geological conditions and petogenesis of the basalt. This study uses observation, field data collection and petrographic analysis. The geomorphology of the research area is composed of denudasional mountain geomorphological units and denudional steep mountain geomorphological units. The stratigraphy of the research area consists of 3 rock units from m to young rocks, namely porphyry basalt, basalt and volcanic breccia units. The developed geological structure is a combination of the Unsystematic and the Amerrung Inverted Fault. The excavation material consists of basalt and rocks mixed with sand. The geological history of the Amerrung area began during the Middle Miocene and eruptions were effusive. Basalt petrogenesis is formed from the presence of volcanic activity that is effusive in the form of basaltic lava flows that undergo a relatively fast freezing process and form basalt. Basalt is a member of the Tefrite Leussite Formation (Tmca) produced by lava and breccia. This formation has a Middle Miocene-Pliocene Age including the Camba Formation.